Analysis of Adoption of Digital Banking Services with The Unified Theory of Acceptance and Use of Technology 3 (UTAUT-3 Model: Analisis Adopsi Teknologi Layanan Digital Banking dengan Model Unified Theory of Acceptance and Use of Technology 3 (UTAUT-3) - Wardana, Laras Kusuma; Bisma, Rahadian (Universitas Negeri Surabaya, 2023)
Digital banking has become a banking service that has been increasingly used since the COVID-19 pandemic. One of the digital banking products in Indonesia is PT Bank Raya Indonesia TBK. This study discusses the level of acceptance of Bank Raya's digital banking by its customers through the mobile application platform on Android and iOS operating systems called RAYA. Using the Unified Theory of Acceptance and Use of Technology 3 (UTAUT-3) model with partial regression analysis (Partial Least Squares/PLS) using SmartPLS software. The PLS analysis technique consists of two stages, namely the measurement model (Outer Model) and the structural model (Inner Model). The study was conducted by distributing research questionnaires to 200 respondents. The results of the study indicate that the higher the level of Performance Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, Habit, and Personal Innovatiness, the greater their influence on the increase in Behavioral Intention to use digital banking services at Bank Raya Indonesia. Additionally, the higher the Facilitating Conditions, Habit, and Personal Innovatiness in using digital banking services, the more it will affect the increase in Use Behavior of digital banking services at Bank Raya Indonesia.